Penerapan Metode Rule Base System Untuk Menentukan Jenis Penyakit Berdasarkan Gejala Pada Ternak Babi Berbasis Website - Antonius Lake; Yoseph P. K. Kelen (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
The rule base system method was used in this research because disease diagnosis in pigs requires a structured approach, where symptoms can be linked to specific rules to produce accurate decisions. The development of this system is in the form of a website that can easily access information and diagnosis anytime and anywhere. This system can help early detection of disease in pigs, reduce the risk of spread, and increase the effectiveness of pig health management in the North Central Timor district. The method used in developing this expert system is a waterfall or what is often called a waterfall which is a classic life cycle. The sequence of developing this method starts from analysis, design, coding, testing, and maintenance stages. A website-based expert system is an application designed to help users diagnose problems or provide recommendations based on the knowledge of an expert that has been modeled in a knowledge base. These systems work by collecting data from users, such as specific symptoms or problems, through a web-based interface, then using an inference engine to analyze that data and generate solutions or suggestions. Based on the results of the User Acceptance Test (UAT) with 5 test categories (menu on the website) and 12 test parameters, overall test results were obtained with an average value of 91%.